Pre-university online examination during pandemic Covid-19: experiences and challenges - Ayu Afiqah Nasrullah (Global Academic Excellence, 2021)
Over the last decade, online examinations have been widely practiced in both the private and government sector. Working professionals preferred the online examination because it provides them with the flexibility of time and location. However, it is not a common practice in educational institutions. Examinations are always conducted in the traditional method through physical attendance, paper, and pen. The outbreak of the covid-19 pandemic and a long duration of lockdown is a game-changer towards assessment and educational approaches that differs from traditional face-to-face methods. Therefore, the purpose of this study is to investigate the first online examination experiences and challenges faced by the foundation of science students in the Preparatory Centre for Science and Technology (PPST), Universiti Malaysia Sabah. A presurvey questionnaire was independently developed to study these purposes. A sample of 252 students from intake session 2019/2020 is affected by this COVID-19 pandemic. In addition, the internet connectivity and readiness of the students for their online examinations are the main challenges that are highlighted in this study.